STRUCTURAL LIMITATIONS OF THE NEW SOCIAL MOVEMENTS ACTIONS - Korolija, Aleksandar (National interest, 2024)
ResumeThe paper conducts conceptual research based on Gramsci's theory of hegemony. The structural limitations of New Social Movements and the lack of transformative strategies are analyzed analytically, in order to answer the research question why social movements failed to achieve changes in the economic and political system through transformative action. After a brief presentation of Gramsci's meaning of hegemony, we move on to the definition of the concept of counter-hegemony, which Gramsci left with an ambiguous meaning. Analysis then moves on to definitions of New Social Movements and their strategies, which are then linked to the concept of counter-hegemony. On this theoretical basis, it is examined whether the resistance practices used by the New Social Movements can bear the name of counter-hegemony. Next step of the analysis moves on to the question of Social Non-Movements and their strategies in order to examine the action of a new type of social movements that is more closely related to the countries of the Middle East. Analyzing the concept and strategies of Social Non-Movements, it is noted that these are social movements that represent a specific Middle Eastern society, however, they are similar to social movements of Western society in that they do not try to bring about deeper transformations of the political and economic structure. Since the New Social Movements are characterized by a shift from the area of production to the area of consumption, it is concluded that the main structural limitations of resistance/counter-hegemonic strategies are based on this transition. By abandoning the question of the organization of the economic system of production, as well as rejecting political society in favor of civil society, these movements remain within the dominant policy paradigm. Fragmentation/atomization with emphasized problems of identity recognition and insistence on the politics of differences, along with the rejection of political organizations and leadership on a conceptual level, rejects the establishment of a new hegemony and thus defines the action of social movements as anti-hegemonic. Therefore, at the very conceptual level, it can be observed that New Social Movements as well as Social Non-Movements do not have deeper intentions to make their strategies counter-hegemonic and to establish a new hegemonic project. On this basis, it is concluded that social movements failed to bring about deeper structural changes in politics and economy because they remained within the framework of the existing hegemonic project.
Keywords: Hegemony; Counter-hegemony; Hegemonic Project; New Social Movements; Social non-movements; Fragmentation; Strategies